2001
DOI: 10.1074/jbc.m104090200
|View full text |Cite
|
Sign up to set email alerts
|

IKKγ/NEMO Facilitates the Recruitment of the IκB Proteins into the IκB Kinase Complex

Abstract: IKK␥/NEMO is an essential regulatory component of the IB kinase complex that is required for NF-B activation in response to various stimuli including tumor necrosis factor-␣ and interleukin-1␤. To investigate the mechanism by which IKK␥/NEMO regulates the IKK complex, we examined the ability of IKK␥/NEMO to recruit the IB proteins into this complex. IKK␥/NEMO binding to wild-type, but not to a kinase-deficient IKK␤ protein, facilitated the association of IB␣ and IB␤ with the high molecular weight IKK complex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 59 publications
2
34
0
2
Order By: Relevance
“…This reasoning is based upon the observations that NF-B cannot be activated in NEMO-deficient cells (24 -26) and overexpression of NEMO can activate IKK in mammalian and yeast systems (30,34,38). In contrast, some workers have described NEMO as an inhibitor of IKK function (29,41), and others have demonstrated that variations in the cellular concentration of NEMO dictate, whether it functions to activate or inhibit NF-B (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reasoning is based upon the observations that NF-B cannot be activated in NEMO-deficient cells (24 -26) and overexpression of NEMO can activate IKK in mammalian and yeast systems (30,34,38). In contrast, some workers have described NEMO as an inhibitor of IKK function (29,41), and others have demonstrated that variations in the cellular concentration of NEMO dictate, whether it functions to activate or inhibit NF-B (32).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that NEMO plays a regulatory role by recruiting the IKK complex to ligated cytokine receptors, where IKKs may be activated by as yet poorly defined mechanisms that possibly include oligomerization, conformational changes, or proximityinduced transphosphorylation events (29 -33). Additionally or alternatively, NEMO may facilitate the recruitment of upstream IKK activators such as kinases that specifically target the activation loops within the catalytic domains of the IKK subunits or enable the interaction of the IKKs with IB proteins (22,34).…”
Section: Proinflammatory Activation Of Nf-b Requires An Upstream Kinamentioning
confidence: 99%
“…Plasmid Constructs-The pCMV5 expression vectors encoding FLAG-or Myc-tagged IKK␣, IKK␤, IKK␥, or p65 or HA-tagged CBP were described previously (32,40,41). Gal4-CBP constructs were kindly provided by Dr. Tucker Collins, and fusions of the VP16 activation domain with IKK␣, IKK␤, or IKK␥/NEMO were constructed in pCMV5 as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…NEMO has multiple protein domains, which are responsible for integrating various signals and binding to adaptor molecules or kinases (IKKα/β) [2]. In addition, NEMO is post-translationally modified by ubiquitination, phosphorylation and SUMOylation in various contexts depending on cell type and stimulus [3].…”
Section: Introductionmentioning
confidence: 99%